Respectable : politics and paradox in making the Morehouse Man - Grundy, Saida, 1982- (University of California Press, 2022)
"The making of a culture of Black male respectability at Morehouse that underlines conservative notions of gender and class--by a former Spelman student who was once 'Miss Morehouse.' How does it feel to be groomed as the 'solution' to a national Black male 'problem?' This is the guiding paradox of Respectable, an in-depth examination of graduates of Morehouse College, the nation's only historically Black college for men. While Black male collegians are often culturally fetishized for 'beating the odds, ' the image of Black male success that Morehouse assiduously promotes and celebrates is belied by many of the realities that challenge the students on this campus. Saida Grundy offers a unique insider perspective: a graduate of Spelman college and a former 'Miss Morehouse, ' Grundy crafts an incisive feminist and sociological account informed by her personal insights and scholarly expertise. Respectable gathers the experiences of former students and others connected to Morehouse to illustrate the narrow, conservative vision of masculinity molded at a competitive Black institution. The thirty-two men interviewed unveil a culture that forges confining ideas of respectable Black manhood within a context of relentless peer competition and sexual violence, measured against unattainable archetypes of idealized racial leadership. Grundy underlines the high costs of making these men--the experiences of low-income students who navigate class issues at Morehouse, the widespread homophobia laced throughout the college's notions of Black male respectability, and the crushingly conformist expectations of a college that sees itself as making 'good' Black men. As Morehouse's problems continue to pour out into national newsfeeds, this book contextualizes these issues not as a defect of Black masculinity, but as a critique of what happens when an institution services an imagination of what Black men should be, at the expense of more fully understanding the many ways these young people see themselves"--